THE EFFECTIVENESS OF USING ENGLISH POP SONGS TOWARD STUDENTS’ LISTENING COMPREHENSION - Delsa Miranty; Eri Rahmawati; Alfi Hasanah (Kantor Bahasa Provinsi Banten and Perkumpulan pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya (PPJB-SIP)., 2018)
The objective of this research was to find out the effectiveness of using English pop songs toward students’ listening comprehension at the tenth grade of SMAN 5 Kota Serang. The population of this research was all the students of the tenth grade of SMAN 5 Kota Serang, and the sample were X Science 4 as experimental class and X Science 3 as control class. The researcher used quantitative method by implementing true experimental design.The instrument of research was the tests: pre and post test. The result of students’ average in pre-test were 45.17 for experimental and 46 for control class. The result of students’ average in post-test were 78 for experimental and 71.67 for control class. It can be concluded that using English pop songs was effective toward students’ listening and the teachers can use English pop songs a a media to overcome students’ difficulty in listening and improve their listening comprehension, too.